1992
DOI: 10.1111/j.1532-5415.1992.tb03646.x
|View full text |Cite
|
Sign up to set email alerts
|

Bedside Assessment of Executive Cognitive Impairment: The Executive Interview

Abstract: These preliminary findings suggest that the EXIT is a valid and reliable instrument for the assessment of executive impairment at the bedside. It correlates well with level of care and problem behavior. It discriminates residents at earlier stages of cognitive impairment than the MMSE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
408
2
7

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 560 publications
(427 citation statements)
references
References 33 publications
6
408
2
7
Order By: Relevance
“…the Stroop test [14]. Other studies found that apathy was significantly associated with executive dysfunctions, evaluated with the Executive Interview [61] and category and letter fluency [45] (In this study patients were treated with Levodopa and their average disease duration was 4.3 years). Dujardin and colleagues [44] evaluated cognitive functions in nondemented PD patients (Average disease duration was 9.4 years and they were treated with Levodopa).…”
Section: Apathymentioning
confidence: 84%
“…the Stroop test [14]. Other studies found that apathy was significantly associated with executive dysfunctions, evaluated with the Executive Interview [61] and category and letter fluency [45] (In this study patients were treated with Levodopa and their average disease duration was 4.3 years). Dujardin and colleagues [44] evaluated cognitive functions in nondemented PD patients (Average disease duration was 9.4 years and they were treated with Levodopa).…”
Section: Apathymentioning
confidence: 84%
“…While the EXIT was originally developed as a measure of executive functions (28), we also considered the EXIT items from the perspective of Miller & Cohen’s later conceptualization of cognitive control, namely, the ‘active maintenance of patterns of activity in the prefrontal cortex that represent goals and the means to achieve them by way of bias signals that promote task-appropriate responding’ (32). Eight of the 25 EXIT items assess the ability to inhibit an automatic behavior, and three items capture error detection or conflict monitoring.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed a spectrum of executive functions with the Executive Interview (EXIT) (28) (range 0–50). The 25 items comprising this screening test are administered in rapid succession with minimal instructions and elicit automatic behaviors and disinhibition and also include modifications of well-known “frontal lobe” tests (number/letter sequencing, Stroop, fluency tests, go/no-go tests, and Luria’s hand sequences).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, participants were 70 and older, diagnosed via Structured Clinical Interview for DSM-IV (First et al, 1995) with current non-psychotic, nonbipolar major depressive disorder (single-episode or recurrent), a 17-item Hamilton Depression Rating Scale (Hamilton, 1960) of 15 or higher, and a Mini Mental State Examination (MMSE) (Folstein et al, 1975) score of 17 or higher. Cognitive function was assessed with the Dementia Rating Scale (Mattis, 2004) and the Executive Interview (Royall et al, 1992). Subjects included in this study had a Mini Mental State Examination of 24 or above.…”
Section: Methodsmentioning
confidence: 99%